2022
DOI: 10.1186/s13031-022-00474-w
|View full text |Cite
|
Sign up to set email alerts
|

Models of care for non-communicable diseases for displaced populations in Iraq: a scoping review

Abstract: Non-communicable diseases (NCDs) are the leading cause of death and disability globally. Their importance in humanitarian settings is increasingly recognised, but evidence about how best to address NCDs in these setting is limited. This scoping review aimed to explore models of NCD care for displaced populations in Iraq, in order to build evidence to design context adapted models of care. A search of key databases (Medline, Embase, Scopus, EconLit, Global Health, Web of Science, and the Iraqi Academic Scientif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…Limited access to healthcare has commonly been noted during active conflicts, influxes of displaced populations, and pandemic related restrictions. Besides, availability of medicines is a crucial aspect of access to healthcare, with public facilities generally performing poorer compared with camp-based primary healthcare services or private healthcare providers in settings with displaced populations [52]. The findings also highlighted significant variations in access rates across different areas and times, even within the same country, supporting the suggestion on the need of understanding local circumstances when designing healthcare models [38,52].…”
Section: Plos Onementioning
confidence: 67%
See 3 more Smart Citations
“…Limited access to healthcare has commonly been noted during active conflicts, influxes of displaced populations, and pandemic related restrictions. Besides, availability of medicines is a crucial aspect of access to healthcare, with public facilities generally performing poorer compared with camp-based primary healthcare services or private healthcare providers in settings with displaced populations [52]. The findings also highlighted significant variations in access rates across different areas and times, even within the same country, supporting the suggestion on the need of understanding local circumstances when designing healthcare models [38,52].…”
Section: Plos Onementioning
confidence: 67%
“…Apart from this, multiple factors hindered access to healthcare, particularly affecting vulnerable populations such as people from minority groups. These factors included the nature and burden of specific diseases, especially NCDs, as well as non-functioning facilities, inadequate staffing, distance to the nearest healthcare facility, and an influx of refugees or returnees, also recently, the COVID-19 lockdowns [37,52]. Limited access to healthcare has commonly been noted during active conflicts, influxes of displaced populations, and pandemic related restrictions.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…In the first phase of the partnership (September 2020 to February 2021), the partners worked on a scoping assessment of the ICRC- and DRC-supported NCD care models in Lebanon and Iraq ( Jaung et al, 2021 , Ansbro et al, 2022 , Schmid et al, 2022 ). In Lebanon, this formative research identified a lack of continuous, standardised, integrated care for NCDs, which was delivered by multiple disparate actors within a historically pluralistic and highly privatised national health system ( Willis et al, 2023 ).…”
Section: The Caja Model As An Ongoing Case Example Of Parallel Tracks...mentioning
confidence: 99%